Effect of tilorone on susceptibility of mice to primary or secondary infection with Listeria monocytogenes. - Gruenewald, R (1976)
Subcutaneous administration of the drug tilorone did not increase the susceptibility of CD-1 male mice to intravenous or intraperitoneal infection with an alpha-toxin-deficient mutant of the Smith diffuse strain strain of Staphylococcus aureus. In contrast, a single injection of this drug greatly increased the susceptibility of mice to an intravenous or an intraperitoneal infection with Listeria monocytogenes, an intracellular parasite. The effects of tilorone, which were maximal when the drug was administered on the day of the listerial challenge or one day thereafter, were reflected by relatively lower mean lethal dose values and enhanced proliferation of Listeria in the spleen and liver. The ability of tilorone, administered at the time of listerial challenge, to decrease the resistance against the challenge was partially abrogated by previous administration of the same drug. Tilorone, administered at the time of immunization with a very small number of viable Listeria, greatly enhanced the potency of the immunization. On the other hand, tilorone, administered to Listeria-immunized mice near to the time of a listerial challenge, slightly reduced the protective effects of the prior immunization.